PLANNING OF MUHAMMADIYAH'S PROSECUTION IN COUNTERING RADICALISM IN KABANJAHE DISTRICT, KARO REGENCY - Wahyu Syahputra; Muhammad Fachran Haikal (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2026)
Radicalism is a challenge in a pluralistic society, so it is necessary to plan for targeted da'wah. This study focuses on examining Muhammadiyah's da'wah planning in countering radicalism in Karo Regency, especially in Kabanjahe District. The researcher used a qualitative method with data collection techniques through participant observation, in-depth interviews, and documentation. Informants were selected using a purposive sampling technique consisting of Muhammadiyah leaders and related autonomous organizations. Then, the data were analyzed using the interactive model of Miles and Huberman through the stages of data reduction, data presentation, data presentation, and drawing conclusions. This study shows that Muhammadiyah's da'wah planning is formulated through da'i cadre development and da'wah training for cadres, da'i assignments to areas with minimal religious understanding, and adapting da'wah material to community conditions. Therefore, Muhammadiyah's da'wah planning plays a role in countering radicalism with a structured, systematic, and contextual approach.